Tinjauan Yuridis Mengenai Pembelaan Terpaksa (Noodweer) Sebagai Alasan Penghapus Pidana (Studi Putusan Nomor: 1/Pid.Sus-Anak/2020/Pn Kpn) - Situmorang, Lina Dwita Damryani; R, Mukhlis; Putri, Adi Tiara (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The reason for the annulment of punishment is a regulation that is primarily aimed at judges. This regulation stipulates the various circumstances of the perpetrator, who have fulfilled the formulation of offenses as stipulated in the Law, who should be convicted, but not convicted If a person who makes a forced defense which is the reason for the annulment of punishment, is later found guilty of his treatment, then this is clearly contrary to the substance of the rule of law itself as in Article 49 of the Criminal Code.This study will examine the subject matter according to the scope and identification of the problem through a normative juridical approach, with the analysis of Decision Number 1 / Pid.Sus-Anak / 2020 / Pn Kpn. Based on the normative research method, the data source used in this study is a secondary data source consisting of 3 legal materials, namely: primary legal materials, secondary legal materials, tertiary legal materials. Data collected from literature study.Then from the results of the research related to the noodweer, there were cases related to forced defense, including in Decision Number 1 / Pid.Sus-Anak / 2020 / Pn Kpn which started from the perpetrator who made a forced defense by committing acts of persecution which led to the death of a person. , was convicted and convicted as a perpetrator of a criminal act of maltreatment and ended in the defendant being convicted by imposing a punishment for Development in an Institution at a Child Welfare Institution for 1 year. This is certainly contrary to Article 49 of the Criminal Code, which should not be punished, especially because the perpetrator is a child.Keywords: Application of Forced Defense (Noodweer) - Decision Number: 1/Pid.Sus-Anak/2020/Pn.Kpn